Concepts and prospects of minimally invasive colorectal cancer surgery. Issue 12 (December 2021) - Merchant, J.; McArthur, D.; Ferguson, H.; Ramcharan, S.
Abstract : It is important that clinical radiologists understand and appreciate the minimally invasive surgery (MIS) options available to surgeons. Operative technologies are constantly evolving, and accurate, informed interpretation of clinical imaging is essential for optimum surgical management. Concurrent advancements in both MIS and radiological staging have certainly improved treatment decisions and outcomes. This article outlines the history, current concepts, evolving techniques, and future prospects of MIS as it pertains to colorectal cancer surgery.